Building maintenance management preliminary finding of a case study in ICYM - Ab Wahab, Yuseni; Hasan Basari, Abd Samad (IDOSI Publications, 2013)
Building Maintenance Management (BMM) is essential to prolong the building life cycle and reduce the company loss. When buildings are neglected, defects can occur which may result in extensive and unavoidable damage to the building fabric or structure. The objective of this study is to identify International College of Yayasan Melaka (ICYM) building maintenance problems. As such, the chosen building needs to be identified before the research start. The defect and the problem face will be collected and noted in a check list. This will be done by questionnaires and distributed to all service users in ICYM building management office and student hostel. Interview sessions and site visit are also conducted to understand the problem encounter. Hence, this paper is focusing on the maintenance management system which the aim is to reduce the downtime of plant items taking into account the possible impact of a failure in terms of cost. The analysis shows that the hostel building contributed to the most problematic area in ICYM. Based on the preliminary finding, it shows that there is a need to propose a systematic building maintenance management.